Insight into the electronic, optical and transport nature of Al2CdX4 (X = S, Se and Te) employing the accurate mBJ approach: Novel materials for opto-electronic devices. (15th November 2021) - Khan, Muhammad Salman; Gul, Banat; Khan, Gulzar; Ghlamallah, Benabdellah; Khattak, Shaukat Ali; Khan, Majid; Khan, Tahirzeb; Ajaz, Muhammad; Zulfiqar, Syed; Muhammad, Wazir
Abstract: Here in this work, we reported results about the electronic, optical and thermoelectric properties of ternary Al2 CdX4 (X = S, Se and Te) chalcogenides by the first principles calculation which are performed within density functional theory. The calculated band profile clearly shows that the valance band (VB) maxima and the conduction band (CB) minima at Γ-point which confirms the three materials as direct-band-gap materials. The small gap value for Al2 CdTe4 as compared to Al2 CdS4 and Al2 CdSe4 indicates the smaller covalent nature in-between the Al and Te atoms. The total and partial density of states along with the optical properties including the real and imaginary part of dielectric function, absorption coefficient, energy loss function, refractive index, reflectivity of these three ternary chalcogenides have also been studied and discussed in detail using the above-mentioned method. The calculated maximum refractive index static values lie in the range of 2–5 eV, confirms that these studied materials can be used in wide-ranged optoelectronic devices which are specifically working in the visible range. Furthermore, the thermoelectric transport parameters such as the Seebeck coefficient, thermal conductivity, specific heat capacity, the power factor, Hall coefficient and the figure of merit were also computed and discussed. Our attained results also reveal the three materials to be efficient candidates for thermoelectric applications. This present work must help in the development of integrated and discrete semiconductor device applications and would make semiconductor materials as a ubiquitous part of our daily life.